SHRM Society for Human Resource Management Complete Study Guide SHRM-CP Exam and SHRM-SCP Exam - Reed, Sandra M. (Sybex, 2022)
Advance your current career or start a new one by obtaining the industry-leading SHRM-CP and SHRM-SCP certifications The Society for Human Resource Management (SHRM) is the world's largest professional association for Human Resources practitioners. Its certifications, while challenging to obtain, open enormous opportunities in the HR field and prove your competence and expertise in the profession. In SHRM Society for Human Resource Management Complete Study Guide: SHRM-CP Exam and SHRM-SCP Exam, veteran HR consultant Sandra M. Reed delivers a comprehensive roadmap to achieving the premier certification for global human resource professionals. You'll get access to Sybex's comprehensive study package, including an assessment test, chapter tests, practice exams, electronic flashcards, and a glossary of key terms. Discover hands-on, practical exercises that prepare you for real-world HR interviews and jobs as you master the technical, leadership, and business competencies you'll need to succeed on the SHRM-CP and SHRM-SCP Exams and in your new HR career. This book also provides: Fully updated information for the latest SHRM Certified Professional and Senior Certified Professional exams Opportunities for new career transitions or advancement with a highly sought-after professional certification Access to Sybex online study tools, with chapter review questions, full-length practice exams, hundreds of electronic flashcards, and a glossary of key terms Perfect for HR leaders who wish to pursue the SHRM Senior Certified Professional or SHRM Certified Professional designations, this study guide also teaches the skills required by anyone seeking to transition into an HR-related role. It offers intuitive and easy-to-follow organization and comprehensive domain coverage ideal for experienced and novice professionals alike.